An extension of the complex–real (C–R) calculus to the bicomplex setting, with applications - Alpay, Daniel; Diki, Kamal; Vajiac, Mihaela (Mathematische Nachrichten, 2024)
In this paper, we extend notions of complex C−R$\mathbb {C} - \mathbb {R}$‐calculus to the bicomplex setting and compare the bicomplex polyanalytic function theory to the classical complex case. Applications of this theory include two bicomplex least mean square algorithms, which extend classical real and complex least mean square algorithms.